2013 IEEE Symposium on Security and Privacy 2013
DOI: 10.1109/sp.2013.20
|View full text |Cite
|
Sign up to set email alerts
|

Ghost Talk: Mitigating EMI Signal Injection Attacks against Analog Sensors

Abstract: Electromagnetic interference (EMI) affects circuits by inducing voltages on conductors. Analog sensing of signals on the order of a few millivolts is particularly sensitive to interference. This work (1) measures the susceptibility of analog sensor systems to signal injection attacks by intentional, low-power emission of chosen electromagnetic waveforms, and(2) proposes defense mechanisms to reduce the risks.Our experiments use specially crafted EMI at varying power and distance to measure susceptibility of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(106 citation statements)
references
References 26 publications
0
96
0
Order By: Relevance
“…Paper [37] identifies a set of safety requirement that can be formally verified against pump software. Measurements in paper [31] show that in free air, intentional EMI under 10 W can inhibit pacing and induce defibrillation shocks at distances up to 1 -2 m on implantable cardiac electronic devices.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper [37] identifies a set of safety requirement that can be formally verified against pump software. Measurements in paper [31] show that in free air, intentional EMI under 10 W can inhibit pacing and induce defibrillation shocks at distances up to 1 -2 m on implantable cardiac electronic devices.…”
Section: Related Workmentioning
confidence: 99%
“…Kevin Fu et al detailed how to reprogram an implantable cardiac defibrillator remotely, causing the victim to receive a malicious shock [10]. Measurements in another paper [31] show that in free air, intentional EMI under 10 W can inhibit pacing and induce defibrillation shocks at distances up to 1 -2 m on implantable cardiac electronic devices. Additionally, harvesting patient data in the region is easily executed via an eavesdropping attack.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since a 2013 paper by Kune et al showed that electromagnetic (EM) signals can be used to cause medical devices to deliver defibrillation shocks [10], there has been a rise in EM, acoustic, and optical signal injection attacks against sensor and actuator systems [7]. Although some papers have focused on vulnerabilities caused by the ADC sampling process itself [2], others have focused on exploiting the control algorithms that make use of the digitized signal.…”
Section: Related Workmentioning
confidence: 99%
“…The integrity of these sensor outputs is crucial, as many security-critical decisions are taken in response to the sensor values. However, specially-crafted adversarial signals can be used to remotely induce waveforms into the outputs of sensors, thereby attacking pacemakers [10], temperature sensors [5], smartphone microphones [9], and carbraking mechanisms [20]. These attacks cause a system to report values which do not match the true sensor measurements, and trick it into performing dangerous actions such as raising false alarms, or even delivering defibrillation shocks.…”
Section: Introductionmentioning
confidence: 99%
“…In case of any malfunction of the vital organs of the body an immediate notification is sent to the personal device to alert the patient to take appropriate measures [5]. For example, consider the glucose level of the patient is very high.…”
Section: Personal Devicementioning
confidence: 99%